Randomized, Placebo‐Controlled Pilot Study of Naproxen During Dental Implant Osseointegration - Hattanas Kumchai; Daniel I. Taub; Ryan E. Tomlinson (Clinical and Experimental Dental Research)
ABSTRACT Objectives Nonsteroidal anti‐inflammatory drugs (NSAIDs) are often prescribed following the placement of dental implants, but the effects of these drugs on the osseointegration process are poorly understood. We designed a randomized, placebo‐controlled pilot study to quantitatively assess the effect of NSAIDs during early implant osseointegration. Materials and Methods Subjects receiving a maxillary dental implant were randomized to take naproxen or placebo for 7 days after the surgery. Implant osseointegration was quantified using Resonance Frequency Analysis device. Implant‐Stability‐Quotient (ISQ) measurement was performed at the time of surgery and at follow‐up visits 1, 4, and 16 weeks after surgery. Periapical radiographs were taken to measure the marginal bone level. Separately, a questionnaire of NSAIDs usage was provided to subjects presenting with early implant failure. Results After 4 weeks, ISQ values increased modestly ( + 1%) in subjects receiving naproxen whereas subjects receiving placebo had a much larger increase in ISQ value (+41%). We observed 55% more marginal bone loss at 4 weeks, and 52% at 16 weeks in the naproxen group compared to the placebo group. These results were not found to have statistically significant between groups (p ≥ 0.05). These effect sizes and variance were used to conduct a power analysis to determine the necessary sample size for future studies. Furthermore, our separate questionnaire study revealed that 68% of our patients with early failed dental implants reported a history of NSAIDs usage after the surgery. Conclusion In conclusion, this pilot study provides effect sizes and sample size estimates for future studies to definitively determine recommendations regarding NSAID usage following dental implant surgery. Nonetheless, our study did not observe any statistically significant differences in ISQ value or marginal bone loss after up to 16 weeks of follow‐up between subjects from naproxen and placebo groups.